Potential and limitations of noise-based surface-wave tomography for numerical site effect estimation: a case study in the French Rhône valley - Lavoué, François; Froment, Bérénice; Gélis, Céline; Boué, Pierre; Chaljub, Emmanuel; Stehly, Laurent; Beauprêtre, Sophie; De Martin, Florent; Gisselbrecht, Loïc; Pilz, Marco; Moiriat, Denis; Cushing, Edward Marc (Comptes Rendus. Géoscience)
In certain geological settings such as sedimentary basins, the ground motion induced by an earthquake may be amplified by local site conditions. Estimating these site effects is important for seismic hazard assessment but can be difficult to do empirically due to the scarcity of site-specific field data in time and space, especially in low-to-moderate seismicity regions where the earthquakes needed for measuring the site effects have long return periods. In this study, we try to overcome these limitations and investigate an alternative approach based on ambient seismic noise and numerical simulations. More specifically, we use a 3D numerical model of seismic properties derived from Ambient Noise Surface-Wave Tomography (ANSWT) for 3D numerical simulations of seismic wave propagation, and consequently for a numerical estimation of seismic amplification in the basin. We illustrate the approach on a target site located in the French Rhône valley, where the Messinian salinity crisis has dug a paleo-canyon which is now filled by soft sediments in direct contact with a harder substratum, thereby providing typical conditions for significant site effects, as also observed by previous studies in the area. This work makes use of two dedicated datasets. On one hand, we use earthquake recordings acquired by a network of broadband stations deployed over the target site over 8 months, in order to estimate seismic amplification in the basin with respect to a rock-site reference via Standard Spectral Ratios (SSR), which we consider as our reference for evaluating our numerical results. On the other hand, we exploit one-month-long ambient noise recordings acquired by a dense array of 400 3C sensors. Prior to this work, this noise data was used to build a 3D shear-wave velocity (VS) model of the target site via ANSWT, and also to estimate seismic amplification via noise-based Standard Spectral Ratios (SSRn). The obtained ANSWT model well reproduces the main geological structures of the basin, with lateral variations of velocities at depth depicting the deeper parts of the basin. However, our simulation results also show that some of its limitations related to surface wave sensitivity and resolution capability have an impact on the numerical amplification predicted in the basin. In particular, this ANSWT model lacks clear basin edges in order to efficiently trap seismic waves in the basin and to generate significant 3D wave propagation effects (diffractions, reflections, and generation of laterally propagating surface waves at the edges of the basin). As a result, the numerical amplification predicted in the ANSWT model remains dominated by a 1D response and does not reproduce the broadband character of the observed amplification at locations affected by significant 3D propagation effects. On the other hand, the numerical amplification predicted in the ANSWT model shows a good agreement with the observations at locations that seem less affected by 3D propagation effects, including in complex regions of the model where lateral variations must be taken into account. Our results therefore contribute to identify and better understand the potential and limitations of using ANSWT models for numerical site effect estimation. This study allows us to propose perspectives for future work to improve the approach, which remains promising for site effect assessment in low- to moderate-seismicity contexts.